Herpes simplex virus capsids assembled in insect cells infected with recombinant baculoviruses: structural authenticity and localization of VP26. - Trus, B L (1995)
Recently, recombinant baculoviruses have been used to show that expression of six herpes simplex virus type 1 genes results in the formation of capsid-like particles. We have applied cryoelectron microscopy and three-dimensional image reconstruction to establish their structural authenticity to a resolution of approximately 2.7 nm. By comparing capsids assembled with and without the expression of gene UL35, we have confirmed the presence of six copies of its product, VP26 (12 kDa), around each hexon tip. However, VP26 is not present on pentons, indicating that the conformational differences between the hexon and penton states of the major capsid protein, VP5, extend to the VP26 binding site.